The problem of naturalism : analytic perspectives, continental virtues - Lightbody, Brian (Lexington Books, 2013)
The Problem of Naturalism: Analytic and Continental Perspectives, investigates how the term naturalism is defined and applied in the philosophic secondary literature from two often competing perspectives: analytic and Continental. The book offers its own justification and explication for naturalism by arguing that naturalism is best thought of as an attitude and not as a methodological or substantive position.